The Use of Drama-Based Pedagogy in Promoting Students' Pronunciation: A Classroom Action Research - Wijaya, Kadek Agus Krisna; Suwastini, Ni Komang Arie; Mahayanti, Ni Wayan Surya (English Education Department STKIP Agama Hindu Singaraja, 2025)
This study aims to improve students' pronunciation through the application of drama-based pedagogy. This study employed a classroom action research design involving 35 ninth-grade students at SMP Negeri 5 Singaraja in the 2024/2025 academic year. The study was conducted in two cycles, and data were collected through pronunciation tests, classroom observations, and interviews with students. The findings revealed a considerable improvement in students' pronunciation skills. The mean score rose from 57.87 on the pretest to 64.30 on post-test 1, and then to 77.21 on post-test 2, indicating consistent improvement in pronunciation aspects such as accuracy, word stress, and intonation. Furthermore, students responded well to the use of drama activities in the classroom, noting that it was enjoyable and encouraging, as well as helping them gain confidence in speaking English. The findings indicate that drama-based pedagogy is an effective and engaging approach to enhance junior high school students’ pronunciation skills.